Khảo sát cấu trúc và tính chất điện tử của một số nhóm nguyên tử NanV (n=1-12) - Nguyễn, Văn HỒng (Trường Đại học Cần Thơ, 2014)
Khảo sát cấu trúc và tính chất điện tử của một số nhóm nguyên tử NanV (n=1-12)